L'Identification de Jésus au Modèle du Hasid Charismatique Galiléen: Les Thèses de Geza Vermes et de Shmuel Safrai Revisitées - Jaffé, Dan (New Testament studies, 2009)
Numerous studies have been undertaken with the objective of putting forward an identity of Jesus according to the Jewish movements of the end of the Second Temple period. Geza Vermes and Shmuel Safrai present an unusual thesis: they suggest that Jesus was a hasid, i.e. a charismatic Galilean prophet. They base themselves principally on the personalities of Hanina ben Dosa and Honi the Circlemaker to draw a behavioral model appropriate to Jesus according to the hasid model. This article explores the theses of these important scholars and refutes them, refusing to see the hasidim of the first centuries as a separate group from the general group of the Sages. Thus Jesus was considered to belong to one of the numerous Pharisee identities.